Selection of potentially optimized trypsin variant with a more hydrophobic cluster active site via a phage display approach - Abdul Kudos, Muhammad Badri; Gissel, Sabrina; Bordusa, Frank (2015)
Protein optimization can generally be obtained by rational enzyme design and directed evolution. Phage display has been used as a method for directed evolution. Trypsin has been studied as a biocatalyst in peptide synthesis despite its usual function in hydrolyzing peptide bonds. The objective of this study is to identify trypsin variants with a more hydrophobic cluster around its active site, potentially yielding higher peptide synthesis products rather than its hydrolysis competitive counterpart. A trypsin variant library displayed by phages with randomization in 5 amino acids located around the active site of the trypsin variant K60E/N143H/E151H/D189K is selected based on a designed immobilization-elution-assay in regard the transamidation reaction model. A preselection stage of recombinant phages was done with MyCUT tag, binding to the immobilized anti-c-myc antibodies. 2 trypsin variants were successfully expressed, purified, characterized and sequenced. Both of them gave a higher accumulative hydrophobicity relative index. This study has shown that selection of a potentially optimized trypsin variant with a more hydrophobic cluster at active site to reduce the hydrolysis products is possible by using the phage display approach.